Bacterial Population of Alfalfa (Medicago sativa L.) Plant Nodules in Koya city: no subtitle - Sara Sherzad Ali; Hikmat Mustafa Masyab; Ayad H.Hasan (Zanco Journal of Pure and Applied Sciences, 2023)
Global food productivity is severely hampered by soil nutrients deficiencies. The use of synthetic nitrogenous fertilizers is widespread cultivation practice to improve agricultural output. Other non-symbiotic endophytic bacteria have also been identified within the same root nodules at the same time as rhizobacteria. It is a common occurrence for non-symbiotic soil microbes to reside in leguminous nodulation. In the current study, Rhizobia and non-symbiotic commensal bacteria that promote plant development were isolated from the native leguminous Medicago sativa. According to our analysis, these non-symbiotic microbes are frequently found inside root nodules and work in concert with rhizobacteria to enhance nodulation and nitrogen fixation in legume crops. The current research work aimed to isolate identification & characterizing root nodulating species from wild alfalfa (Medicago sativa. L) plant nodules collected from different regions of Koya city in the Erbil district. Isolation of these species was done by culturing on YEMA (Yeast Extract Mannitol Agar) medium and incubation period of 48 hours at 30 °C. The sample identification was processed using standard microbiological and biochemical techniques as well as 16S rDNA partial sequence and nifH gene. Results showed that thirty nodule samples yielded a total of two Rhizobium species isolates, one of them was recorded in NCBI as a new strain. The others were found to be Pseudomonas and Enterobacter, Rahnella and Erwinia respectively. The findings suggested that lateral gene transfer (LGT) between non-symbiotic endophytic bacteria and rhizobacteria may have taken place.